Primary mathematics : Extending knowledge in practice - Hansen, Alice (British : Learning Matters Ltd, 2008)
The acquisition of subject knowledge, and how to translate this into effective teaching is a major concern for many on initial teacher training courses. This book extends trainees' knowledge of mathematics in a manner which enables them to use it more actively in planning and implementing lessons.
Includes references and index.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Mathematics teachers -- training of -- Great Britain; EDUCATION -- Teaching Methods & Materials -- Mathematics